PENGEMBANGAN MEDIA E-BOOK INTERAKTIF BERBASIS BOOK CREATOR MENGGUNAKAN MODEL PBL PADA PEMBELAJARAN IPAS DI KELAS IV SEKOLAH DASAR - Andina, Reviola; Arwin; Hamimah; Inggria Kharisma (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This research is motivated by the demands of the digital era, which require teachers to be innovative and utilize technology to achieve the goals of the continuously evolving Kurikulum Merdeka. However, there are limitations faced by teachers in the learning process within the digital era. This study employs the Research and Development (R&D) method using the ADDIE model, which consists of five stages: Analysis, Design, Development, Implementation, and Evaluation. Data collection was obtained through observations, interviews, and validation questionnaires provided to three experts (content, language, and media), as well as practicality response questionnaires given to teachers and students at four schools: UPTD SD Negeri 03 Tujuah Koto Talago, UPTD SD Negeri 05 Tujuah Koto Talago, UPTD SD Negeri 06 Tujuah Koto Talago, and UPTD SD Negeri 09 Tujuah Koto Talago. The results indicate that the developed interactive e-book media has met the feasible and applicable criteria. Based on the validity tests, the results obtained from the content expert reached 93.3% (very valid), language validation 91.34% (very valid), and media validation 80% (valid). The practicality test results from teachers at various schools showed an average percentage above 80% (very practical), and the student practicality questionnaires showed an average above 89% (very practical). Based on this data analysis, it can be concluded that the interactive e-book media based on Book Creator using the PBL model for IPAS learning in Grade IV has been declared very valid theoretically and very practical operationally.